2022
DOI: 10.1016/j.eclinm.2021.101215
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative recurrence prediction in pancreatic ductal adenocarcinoma after radical resection using radiomics of diagnostic computed tomography

Abstract: Background The high recurrence rate after radical resection of pancreatic ductal adenocarcinoma (PDAC) leads to its poor prognosis. We aimed to develop a model to preoperatively predict the risk of recurrence based on computed tomography (CT) radiomics and multiple clinical parameters. Methods Datasets were retrospectively collected and analysed of 220 PDAC patients who underwent contrast-enhanced computed tomography (CE-CT) and received radical resection at 3 instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Accordingly, the radiomics model in the present study did not demonstrate sufficient predictive ability for the early recurrence of pancreatic cancer. A previous study attempted to include perilesional information by increasing the segmentation boundary; however, this approach could not take into account broader contextual information, such as adjacent organ invasion and vascular abutment, which were also demonstrated to be significant in the present study [ 42 ]. One promising approach for enhancing radiomics-based models involves providing additional information, such as radiologic features and clinical data, that cannot be obtained from a segmented image alone [ 47 ].…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, the radiomics model in the present study did not demonstrate sufficient predictive ability for the early recurrence of pancreatic cancer. A previous study attempted to include perilesional information by increasing the segmentation boundary; however, this approach could not take into account broader contextual information, such as adjacent organ invasion and vascular abutment, which were also demonstrated to be significant in the present study [ 42 ]. One promising approach for enhancing radiomics-based models involves providing additional information, such as radiologic features and clinical data, that cannot be obtained from a segmented image alone [ 47 ].…”
Section: Discussionmentioning
confidence: 94%
“…Although the pathology test kit used in our study was different from their pathology test kits, our results were comparable to their results. The prediction model can be constructed using only CT images without There has been a recent increase in interest in studying the peritumoral region as the immediate environment of the tumor mass, the microenvironment, and tumor habitat can harbor variable diseasespecific factors (Zhang et al 2012, Li et al 2022. Parra et al showed that NSCLC histologic specimens had higher numbers of TAICs in the peritumoral compartment than in the intratumoral region, and PD-L1 expression was correlated with TAICs for adenocarcinoma and squamous cell carcinoma (Parra et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Then, ANN and LR models were employed to develop the ITV model, PTV model, combined model, clinical model, and radiomics-clinical model. Radiomics-clinical model outperformed other models in predicting 1-year recurrence (AUC 0.764 for validation set) and 2-year recurrence (AUC 0.773 for validation set) 224 .…”
Section: Ai In Prognosismentioning
confidence: 91%
“…These facts make it challenging to predict the prognosis of PC. Due to its excellent computational power, AI was used to analyze PC prognoses, including survival time 204 - 221 , recurrence risk 78 , 221 - 224 , metastasis 225 - 230 , therapy response 79 - 81 , 231 - 240 , etc.…”
Section: Ai In Prognosismentioning
confidence: 99%